The expectation of TVE student teachers to choose teaching as a career - Ismail, Normala; Bakar, Ab. Rahim; Hamzah, Ramlah (2012)
In recent year, there has been an increasing interest in factors which influenced a student teacher to consider teaching as a career. The expectation perceived by Technical and Vocational Education, (TVE) student teachers becomes the factor that influenced them to enter the teaching profession. This paper identified the expectation of TVE student teachers to choose teaching as a career. The survey study conducted using 300 TVE student teachers from four public universities involved. The findings of the study reveal that there was a significant different between expectation of TVE student teachers to choose teaching, (t=4.33, p<.05). By determining the expectation of TVE student teachers to choose teaching as a career, it will indirectly enchance the recruitment and retain teacher longer in the teaching profession.